The photo-physicochemical properties and in vitro sonophotodynamic therapy activity of Di-axially substituted silicon phthalocyanines on PC3 prostate cancer cell line - Atmaca, Goknur Yasa; Aksel, Mehran; Keskin, Bahadir; Bilgin, Mehmet Dincer; Erdogmus, Ali (ELSEVIER SCI LTD, 2021)
In this study, novel silicon phthalocyanines complexes have been synthesized, characterized and compared their antitumor efficiency of photodynamic, sonodynamic, sonophotodynamic on prostate cancer cells. Sonophotodynamic therapy (SPDT), a combination of photodynamic therapy (PDT) and sonodynamic therapy (SDT), is a new and promising method for the treatment of cancer cells. Although it is known that SPDT therapy has improved potential therapeutic result, the development of this method by working with different sensitizers has been lacking in the literature. To the best of our knowledge, this paper is the first study in the literature to calculate the photochemical properties of synthesized molecules and compare the results of photodynamic, sonodynamic and sonophotodynamic therapies on prostate cancer cells. In this study, new water soluble sensitizers with the different properties of linker hetematom (O or S) were synthesized, characterized and analyzed their photophysicochemical properties. Then, the effects of sonodynamic, photodynamic and sonophotodynamic on these sensitizers were examined in vitro on prostate cancer using PC3 cells. For this purpose, the cells were incubated with various concentrations of chemicals and subjected to ultrasound and/or light irradiation. According to MTT results, the sensitizers were showed quite efficiency for sonodynamic, photodynamic and sonophotodynamic therapies and decreased cell viability when compared with control group. Also apoptosis measurement data shows that the sensitizers (1a, 1b) would produce much better effects by combination sonodynamic and photodynamic therapies, especially the measurement of apoptotic cells in complex 2a reached 95% after SPDT therapy. As a result, it is seen that SPDT is a combination which has enhanced the therapeutic outcome.
Keywords: Phthalocyanine; Silicon; Sonophotodynamic therapy; Prostate cancer cell line; PHOTODYNAMIC THERAPY; PHOTOSENSITIZERS; DERIVATIVES; Chemistry; Engineering; Materials Science